EFEKTIVITAS IKLAN TERHADAP KEPUTUSAN WISATAWAN MEMBELI TIKET PESAWAT DI TRAVELOKA.COM - Kristina Angelina Gultom; NMS. Wijaya; Ni Putu Eka Mahadewi (Jurnal IPTA (Industri Perjalanan Wisata), 2021)
This research was conducted to analyze the Effectiveness of Advertising on Tourist Decisions in Purchasing Flight Ticket on the Online Travel Agent Traveloka.com using the EPIC Model and Direct Rating Method (DRM) and its Effect on the Flight Ticket Purchase Decision partially and simultaneously. This research method uses data collection techniques in the form of observation, questionnaires, and literature study. The technique of determining the sample using a purposive sampling method. The data analysis technique used quantitative descriptive analysis and multiple linear regression analysis. The results of this study indicate that Traveloka.com advertising using the EPIC Model method in measuring the advertising communication approach has been effective in introducing products in the form of flight tickets with a value of 4,008 and the Direct Rating Method in measuring good value advertising messages in conveying messages with a value of 79.44. EPIC Model's multiple linear regression analysis on Purchasing Decisions has a positive effect with a significant value of 0.015, the Direct Rating Method has a positive effect with a significant value of 0.003, while simultaneously or simultaneously, the Effectiveness of Advertising on Purchasing Decisions has a positive and significant effect. Based on the results obtained, the effectiveness of advertising can have an influence on purchasing decisions made by buyers through advertisements that contain information about existing products.